2018
DOI: 10.1051/epjap/2018180227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pulsed electrodeposition parameters on the properties of zinc oxide thin films to improve the photoelectrochemical and photoelectrodegradation efficiency

Abstract: Zinc oxide (ZnO) thin films were synthesized on ITO glass substrates by electrochemical deposition from a nitrate solution. The deposition potential, bath temperature and annealing temperature were fixed at −1.1 V versus SCE, 80 and 400 °C, respectively. Firstly, we prepared the ZnO thin films by two different electrochemical methods: direct (DE) and pulsed electrodeposition (PE). The results indicate that pulse electrodeposition improves the properties of ZnO thin films compared to direct electrodeposition te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Compared to direct current (DC), PC has proved to be an interesting alternative for improving/modifying coating quality [34,35]. In the pulse current method, the operational variables under control are peak current density (Ip), average current density (Ia), on-time (ton), off-time (toff), pulse frequency (f) and duty cycle (q).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to direct current (DC), PC has proved to be an interesting alternative for improving/modifying coating quality [34,35]. In the pulse current method, the operational variables under control are peak current density (Ip), average current density (Ia), on-time (ton), off-time (toff), pulse frequency (f) and duty cycle (q).…”
Section: Introductionmentioning
confidence: 99%
“…During time Off, the bath's ions move to a deprived area. After a short delay, the pulse is turned on again, and this time there are more uniformly dispersed ions available for deposition into the substrate [35].…”
Section: Film Preparationmentioning
confidence: 99%
“…Zinc oxide (ZnO) is an interesting semiconducting material for photocatalytic water purification and has been the subject of many studies . Although its large scale use still suffers from important limitations such as limited efficiency under visible light due to a band gap of about 3.2–3.4 eV and photocorrosion, recent developments have demonstrated that ZnO nanoparticles have a tremendous potential for water purification applications using a photocatalytic approach, which is simpler than a photoelectrocatalytic process . Furthermore, ZnO has the benefits of being cheap and mechanically stable.…”
Section: Introductionmentioning
confidence: 99%